PENERAPAN VALUE ENGINEERING PADA PEMBANGUNAN GEDUNG STUDI KASUS : PEMBANGUNAN GEDUNG E UNIVERSITAS DHYANA PURA - Dewi, Anak Agung Diah Parami; Putera, I Gusti Agung Adnyana; Kesuma, I Kadek Adi (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 24, No. 1, Januari 2020DO - 10.24843/JITS.2020.v24.i01.p09, 2020)
C onstruction project activities face many problems associated with material and which results in cost overun . To avoid this, a method is needed namely Value Engineering. The purpose of this study is to seek the best alternatives to produce lower costs without reducing the function and quality of work on the E Building project at Dhyana Pura University on Jalan Raya Padang Luwih, Dalung, North Kuta. In determining alternatives, a brainstorming process was conducted through observation and interviews. From the alternatives obtained then an assessment is carried out with Value Engineering to obtain the best alternative. Based on the results of Value Engineerin , floordeck is the best alternative used on first floor  to the highest floor . By using   floordeck plate , it costs Rp. 1,000,298,413.32 .  It can save Rp. 531,703,624.12 or 34.71% of the initial cost of Rp. 1,532,002,037.44. The time needed to complete the work is 45 days or 66.90%  of the initial time period of 127 days.